Flexible CO2 sensors based on carbon nanotubes - Liu, Yu (2016)
CO2 has an enormous impact on the environment. Increase in CO2 concentration in the atmosphere is found to be a key factor that degrades air quality significantly and leads to global warming. Thus, CO2 concentration has become an important indicator to tell the degree of air pollution. How to detect CO2 at a very low concentration is a hot research topic. Current CO2 sensors have many problems to be solved. For example, poor selectivity, high-cost and bad recovery. Thus, there is a great demand for a new type CO2 sensor. In this master of science project, two types of flexible substrates, i.e. polyimide (PI) plastic and cellulose paper, are used to fabricate flexible single-walled carbon nanotubes (SWCNT) network based CO2 sensors. Their sensitivities to CO2 are largely improved by attaching amine-containing groups to the SWCNT network. The influences of humidity on their sensing performance are analyzed. Moreover, the sensors are tested in both nitrogen and air background to investigate the effects of oxygen on the CO2 sensing responses. Our results suggest that PI plastic and cellulose paper are of good properties for flexible CO2 SWCNT network sensors. Amino containing groups are shown to be essential to enhance the sensitivity of the flexible CO2 sensors. The sensor on PI substrate has shown a sensitivity of 5.3% while the sensor on the paper substrate has a sensitivity of 8.8%. Also, it has been shown that humidity has an impact on the sensing responses. The sensitivity increases with increasing humidity. Lastly, we find that these CO2 sensors are insensitive to oxygen concentration up to 15000 ppm in air. However, further efforts must be made to improve the recovery of these flexible CO2 sensors. In addition, the signal to noise ratio of the sensors must also be improved.